Potret Kehilangan pada Lirik Lagu dan Film Kukira Kau Rumah: Kajian Sastra Bandingan - Ashpia Latifah (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2023)
Loss is something that cannot be separated from the life of every human being. Issues of loss are not only present in real everyday life, but are also present in a literary work, one of which is present in the song lyrics and film Kukira Kau Rumah. Therefore, this study aims to describe how the portrait of loss is contained in the lyrics of the song and film Kukira Kau Rumah along with the sureeche responses contained therein. This research is descriptive qualitative by using comparative literature method and literary psychology approach as well as the theory of depression according to Rando. The data sources in this study are song lyrics and the film Kukira Kau Rumah. The data collection technique was carried out by listening to notes through song lyrics and the film Kukira Kau Rumah. The data analysis technique was carried out by listening to and listening to the lyrics of the song Kukira Kau Rumah, watching and listening to the film Kukira Kau Rumah, marking the parts that show loss and depression, classifying the data, and concluding the results. The results of the study show that there are two portrait forms of loss in the lyrics of the song and film Kukira Kau Rumah, including loss of self aspects (loss of self) and loss of the closest person or loved one. In addition, 12 positive responses were found including 4 avoidance positive responses, 4 confrontation positive responses, and 4 comfort positive responses. Based on this, it can be seen that the lyrics of the song Kukira Kau Rumah influence the form of the film Kukira Kau Rumah by covering the agreements and differences contained therein.